2018
DOI: 10.24326/asphc.2018.6.17
|View full text |Cite
|
Sign up to set email alerts
|

THE ACTIVITY OF ESSENTIAL OILS OBTAINED FROM SPECIES AND INTERSPECIES HYBRIDS OF THE Mentha GENUS AGAINST SELECTED PLANT PATHOGENIC BACTERIA

Abstract: Plant essential oils of six aromatic herb species and interspecies hybrids of the family Lamiaceae – chocolate mint (Mentha piperita × ‘Chocolate’), pineapple mint (Mentha suaveolens ‘Variegata’), apple mint (Mentha × rotundifolia), spearmint (Mentha spicata), orange mint (Mentha × piperita ‘Granada’) and strawberry mint (Mentha × villosa ‘Strawberry’) – were investigated for antimicrobial effects against plant pathogenic bacteria: Agrobacterium tumefaciens, Pseudomonas syringae pv. syringae and Xanthomonas ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although, very few studies were conducted to assess efficacy of essential oils from the medicinal plants, including those used in this study (such as M. spicata, T. spicata var. spicata and T. serpyllum) against crown gall disease agent R. radiobacter (Basim et al, 2000;Ateeq-ur-Rehman et al, 2009;Schollenberger et al, 2018), to the best of our knowledge there is no research on the evaluation of the efficacy of essential oils used in the present study against gall forming bacterial species such as P. savastanoi pv. savastanoi and P. savastanoi pv.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Although, very few studies were conducted to assess efficacy of essential oils from the medicinal plants, including those used in this study (such as M. spicata, T. spicata var. spicata and T. serpyllum) against crown gall disease agent R. radiobacter (Basim et al, 2000;Ateeq-ur-Rehman et al, 2009;Schollenberger et al, 2018), to the best of our knowledge there is no research on the evaluation of the efficacy of essential oils used in the present study against gall forming bacterial species such as P. savastanoi pv. savastanoi and P. savastanoi pv.…”
Section: Resultsmentioning
confidence: 93%
“…Earlier studies have demonstrated the antibacterial activities of essential oils obtained from different plant species to retard and inhibit not only the growth of gal forming bacterial disease agent R. radiobacter (Basim et al, 2000;Iacobellis et al, 2005;Ateeq-ur-Rehman et al, 2009;Mohan et al, 2011;Melkani et al, 2011;Moghaddam et al, 2014;Badawy and Abdelgaleil, 2014;Schollenberger et al, 2018;Turker et al, 2018;Ben Hsouna et al, 2019) but also other plant pathogenic bacterial disease agents such as Pseudomonas syringae pv. syringae (Schollenberger et al, 2018;Moghaddam et al, 2014), Xanthomonas arboricola pv. corylina (Schollenberger et al, 2018), Ralstonia solanacearum (Moghaddam et al, 2014), Pseudomonas syringae pv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, terpenoids have been recognized as interesting molecules for their antimicrobial activity, making EOs suitable candidates for bacterial control [7,8]. However, the composition of EOs varies depending on the growth conditions of plants, including the climate, plant genetics, cultivation practices, and physiological condition of plants [9]. The EOs derived from plants belonging to the Lamiaceae family, e.g., genera Mentha, Melissa, Salvia, Thymus, and Origanum, showed effective control of numerous economically important phytopathogenic bacteria [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%